Productivity and Reproductive Performance of Mixed-Age Ewes across 20 Years of Selection for Ultrafine Wool in Uruguay - Ramos Z; Blair HT; De Barbieri I; Ciappesoni G; Montossi F; Kenyon PR (MDPI (Basel, Switzerland), 2021)
This study reports the phenotypic trends for wool, growth, and reproductive traits in mixed-age ewes after twenty years of genetic selection. Data were obtained from the Merino nucleus flock in Uruguay between 1999 and 2020. Overall, the aim of this selection flock was to reduce the fiber diameter (FD) and increase both the clean fleece weight (CFW) and live weight (LW). Data on ewe wool traits, LW, body condition score (BCS), the total number of lambs weaned (TLW), and the total LW of lambs weaned (TWW) across all lambing opportunities (1–8 mating seasons) were analyzed. Between 1292 and 2063 ewes were measured, depending on the trait considered. Ewe FD decreased by approximately 3 µm (19–16 µm), whereas greasy fleece weight (GFW) increased by 0.2 kg. This improvement in wool traits was accompanied by increases in LW at mating (3 kg), decreases in BCS at mating (approximately by 1 unit), and a small positive change in TWW across years. This study demonstrated that increasing farmer income by selecting for finer wool, heavier fleeces, and heavier animals can be obtained without compromising ewe lifetime reproduction.
Keywords: sheep; wool; selection; live weight; body condition score; lifetime reproduction